Geometrically nonlinear transient analysis of thick deep composite curved beams with generalized differential quadrature method - Kurtaran, Hasan (Elsevier Sci Ltd, 2015)
This article focuses on geometrically nonlinear transient analysis of thick deep laminated composite curved beams with generalized differential quadrature method. Generalized differential quadrature method is coupled with, the weak form of the equation of motion. Virtual work principle is used to derive the equation of motion. Spatial derivatives in the equation of motion are expressed with generalized differential quadrature method. Geometric nonlinearity is considered through Green-Lagrange nonlinear strain displacement relations that are derived using elasticity theory equations. First-order shear deformation theory is used to consider the transverse shear effect. Time integration of the equation of motion is carried out using Newmark average acceleration method. Several problems from the literature are solved with the proposed method and results are compared. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Generalized differential quadrature; Transient analysis; Geometric nonlinearity; Laminated composite; Curved beam